Fuel properties and ageing of bioslurry prepared from glycerol/methanol/bio-oil blend and biochar. (15th July 2016) - Gao, Wenran; Zhang, Mingming; Wu, Hongwei
Highlights: Fuel properties of glycerol/methanol/bio-oil/biochar (GMBB) bioslurry fuels are investigated. HHV, density and surface tension of GMBB bioslurry fuels increase with biochar loading level. Methanol and glycerol slow down the ageing of the GMBB bioslurry fuels. Methanol and glycerol reduces the leaching of AAEM species from biochar during bioslurry ageing. Abstract: This study investigates the fuel properties and ageing of a series of bioslurry fuels prepared from glycerol/methanol/bio-oil (GMB) blend and biochar at different biochar loading levels (up to 16.7 wt%). The GMB/biochar (GMBB) bioslurry fuels generally exhibit non-Newtonian and thixotropic behaviour, especially those at high biochar to GMB blend ratios (2:20–4:20). An increase in biochar loading level also increases the HHV, density and surface tension of the GMBB bioslurry fuels. Compared to the bio-oil/biochar (BB) bioslurry fuels at the same biochar loading level, the GMBB bioslurry fuels have much lower viscosity, water content and total acids number (TAN). Both the GMBB and BB bioslurry fuels have increasing viscosity, decreasing water content and TAN with increasing biochar to liquid ratio. Ageing leads to decreases in the TAN and viscosity but an increase in water content of the GMBB slurry fuels. The leaching of AAEM species from biochar in the GMBB bioslurry fuels increases with ageing. The presence of methanol and glycerol in the GMBB slurry fuels slow down the ageing and also leads to less leaching of AAEM species from biochar after accelerated ageing.